Method for enriching precious metal

By mixing precious metal-containing materials with reducing agents and calcium fluxing agents and melting to form an olivine phase, the method enhances precious metal enrichment while reducing environmental impact and operational costs.

CN120311034APending Publication Date: 2025-07-15CNGR ADVANCED MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510399463.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The prior art has problems such as heavy metal pollution, low capture rate and low enrichment multiple in the process of precious metal recycling, and the wet treatment cost is high and it cannot be effectively reused.

Method used

In the presence of a reducing agent, the noble metal-containing material, smelting additive and calcium-containing slag-making agent are mixed and melted to form a molten slag containing olivine phase and a precious metal-enriched phase, and further purified by acid leaching and oxidation reaction to form a nickel-containing solution and precious metal concentrate.

Benefits of technology

It increases the enrichment multiple of precious metals, reduces the environmental impact, simplifies the process flow, reduces the generation of wastewater, and achieves efficient precious metal recycling, with few equipment configurations and a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120311034A_ABST
    Figure CN120311034A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of precious metal metallurgy, and discloses a method for enriching precious metal. The method comprises the following steps: in the presence of a reducing agent, contacting and mixing a precious metal-containing material, a smelting auxiliary agent and a calcium-containing slag former to obtain a mixture; and the mixture is subjected to smelting treatment, and olivine phase-containing molten slag and a precious metal-containing enriched phase are obtained. According to the method for enriching the precious metal, the melting temperature and the viscosity during melting can be reduced, the slagging success rate is high, and the molten slag containing the olivine phase and the enriched phase containing the precious metal are obtained; and moreover, the molten slag and the enriched phase are simple in phase splitting, enrichment of the precious metal is further promoted, and the enrichment multiple of the precious metal is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of precious metal metallurgy, and specifically relates to a method for enriching precious metals. Background Art

[0002] Precious metals often occur in nature in association with other minerals. During the extraction process of related minerals, precious metals usually exist in related products / by-products / wastes. If not effectively recovered, it will not only cause environmental pollution but also lead to waste of resources.

[0003] In related technologies, the recovery of precious metals by pyrometallurgy can achieve the recovery of some precious metals, but there are still problems such as heavy metal pollution, low capture rate, and low enrichment multiple. Summary of the Invention

[0004] The purpose of this application is to provide a method for enriching precious metals to improve the enrichment effect of precious metals and reduce the potential impact on the environment.

[0005] To achieve the above purpose, this application provides a method for enriching precious metals, which includes:

[0006] In the presence of a reducing agent, contacting and mixing a precious metal-containing material, a smelting aid, and a calcium-containing slag-forming agent to obtain a mixed material;

[0007] Smelting the mixed material to obtain a molten slag containing olivine phase and an enriched phase containing precious metals.

[0008] The method for enriching precious metals provided by this application contacts and mixes and smelts a precious metal-containing material, a smelting aid, and a calcium-containing slag-forming agent to obtain a molten slag containing olivine phase and an enriched phase containing precious metals. The molten slag containing olivine phase has low viscosity and is easy to phase-separate from the enriched phase, significantly increasing the enrichment multiple of precious metals. In addition, the smelting process has a simple process flow, few equipment configurations, easy control of process parameters, no wastewater production, and a wide application range, solving the problems of high cost of using chlorine to remove base metals in the wet process, high cost of wastewater treatment after mixing system anions, and inability to be recycled.

[0009] Optionally, the smelting aid includes at least one of an iron-containing material and a silicon-containing material.

[0010] Optionally, the addition amounts of the precious metal-containing material, the smelting aid, and the calcium-containing slag-forming agent satisfy: based on the total weight of FeO, SiO2, and CaO, the content of FeO is 30-60 wt%, the content of SiO2 is 15-40 wt%, and the content of CaO is 10-30 wt%.

[0011] Optionally, the method satisfies at least one of the following conditions:

[0012] A. The olivine phase is 2(Fe, Ca)O-SiO2 phase;

[0013] B. The precious metal-containing material is selected from at least one of hematite slag, anode slime, smelting slag, and associated precious metal ore;

[0014] C. The composition of the precious metal-containing material includes: Fe 15-25 wt%, Ni 1-2.5 wt%, Si 10-20 wt%, Cu 0.05-0.4 wt%, precious metal 500-2000 g / t;

[0015] D. The composition of the precious metal includes: Pt 560-580 g / t, Pd 420-430 g / t, Ag 40-45 g / t, Au 90-93 g / t, Ir 71-73 g / t, Rh 84-86 g / t.

[0016] Optionally, the method satisfies at least one of the following conditions:

[0017] A. The calcium-containing slag-forming agent is calcium oxide;

[0018] B. The silicon-containing material is silicon dioxide;

[0019] C. The iron-containing material is selected from at least one of hematite, matte nickel, nickel matte, nickel iron, scrap iron, and nickel slag;

[0020] D. The composition of the hematite includes: Fe 60-65 wt%, Ni 1-3 wt%, Si 0.01-0.04 wt%, Cu 0.1-0.2 wt%;

[0021] E. The composition of the matte nickel includes: Fe 52-56 wt%, Ni 17-20 wt%, Si 0.01-0.04 wt%, Cu 0.02-0.05 wt%;

[0022] F. The composition of the nickel matte includes: Fe 3.5-3.9 wt%, Ni 68-72 wt%, Si 0.008-0.015 wt%, Cu 0.1-0.15 wt%.

[0023] Optionally, the method satisfies at least one of the following conditions:

[0024] A. The reducing agent is selected from at least one of activated carbon, graphite, coke powder, and coal powder;

[0025] B. Based on the total weight of the precious metal-containing material, the dosage of the reducing agent is 1-10 wt%;

[0026] C. Based on the total weight of the mixture, the dosage of the precious metal-containing material is 40 - 80 wt%, the dosage of the smelting aid is 15 - 50 wt%, and the dosage of the calcium-containing slag-forming agent is 5 - 10 wt%;

[0027] D. The conditions of the smelting treatment include: the smelting temperature is 1100 - 1300 °C;

[0028] E. The conditions of the smelting treatment include: the smelting time is 4 - 6 h.

[0029] Optionally, the method satisfies at least one of the following conditions:

[0030] A. It further includes contacting an acidic substance with the enrichment phase to carry out an acid leaching reaction to obtain an acid leaching product;

[0031] B. The steps of the acid leaching reaction include: preparing the enrichment phase into a slurry, and contacting the slurry with an acidic substance to carry out an acid leaching reaction;

[0032] C. The acidic substance is selected from at least one of hydrochloric acid, nitric acid, and sulfuric acid with a concentration ≥ 98 wt%;

[0033] D. The addition amount of the acidic substance makes the initial pH value of the system 0 - 2.5;

[0034] E. The conditions of the acid leaching reaction include: the temperature is 80 - 100 °C, and the time is 1 - 2 h.

[0035] Optionally, the method satisfies at least one of the following conditions:

[0036] A. It further includes contacting the acid leaching product with an oxidant to carry out an oxidation reaction to obtain a nickel-containing solution and a precious metal concentrate;

[0037] B. The oxidant is selected from at least one of ozone, sodium persulfate, and sodium peroxydisulfate;

[0038] C. The flow rate of the introduced ozone is 200 - 600 mL / min;

[0039] D. The weight ratio of the acid leaching product to the sodium persulfate is 1:0.8 - 1.2;

[0040] E. The weight ratio of the acid leaching product to the sodium peroxydisulfate is 1:0.8 - 1.2;

[0041] F. The time of the oxidation reaction is 6 - 8 h.

[0042] Optionally, the method further includes: performing impurity removal treatment on the nickel-containing solution to obtain a nickel salt solution.

[0043] Optionally, the noble metal content in the noble metal concentrate ≥ 95 kg / t.

[0044] Additional aspects and advantages of the present application will be given in part in the following description, become apparent in part from the following description, or be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Partially shows a schematic block diagram of the process of enriching noble metals in some embodiments;

[0046] Figure 2 Shows the molten slag containing olivine phase and the assay button obtained in Example 1;

[0047] Figure 3 Shows the molten slag containing olivine phase and the assay button obtained in Example 2;

[0048] Figure 4 Shows the molten slag containing olivine phase and the assay button obtained in Example 3;

[0049] Figure 5 Shows the molten slag containing wollastonite phase and the assay button obtained in Comparative Example 1;

[0050] Figure 6 Shows the molten slag containing wollastonite phase and the assay button obtained in Comparative Example 2;

[0051] Figure 7 Shows the molten slag containing olivine phase and the assay button obtained in Comparative Example 3;

[0052] Figure 8 Shows the XRD pattern of the molten slag containing olivine phase obtained in Example 1. DETAILED DESCRIPTION

[0053] The endpoints and any values disclosed herein are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and a single point value, and between single point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

[0054] As used herein, the terms "comprising", "including", "having", "containing" or any other variation thereof are intended to cover non-exclusive inclusion. For example, a composition, step, method, article or device containing the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article or device.

[0055] In this text, wt% refers to weight percentage, and unless otherwise specified, the percentages mentioned are all by mass.

[0056] Based on the above problems, as described above, the present application provides a method for enriching precious metals, which includes:

[0057] In the presence of a reducing agent, contacting and mixing a precious metal-containing material, a smelting aid, and a calcium-containing slag-forming agent to obtain a mixture;

[0058] Smelting the mixture to obtain a molten slag containing an olivine phase and an enriched phase containing precious metals.

[0059] In the method for enriching precious metals provided by the present application, by smelting a precious metal-containing material, a smelting aid, a calcium-containing slag-forming agent, and a reducing agent, controlling the formation of an olivine phase in the molten slag is beneficial to the separation of the molten slag and the enriched phase, and is also beneficial to the easier entry of precious metals into the enriched phase, significantly increasing the enrichment multiple of precious metals.

[0060] In some embodiments, the smelting aid includes at least one of an iron-containing material and a silicon-containing material. The materials included in the smelting aid can be adjusted according to the composition of the precious metal-containing material. For example, when the proportion of SiO2 contained in the precious metal-containing material meets the smelting requirements, the smelting aid may not include a silicon-containing material.

[0061] In some embodiments, the addition amounts of the precious metal-containing material, the smelting aid, and the calcium-containing slag-forming agent satisfy: based on the total weight of FeO, SiO2, and CaO, the content of FeO is 30 - 60 wt%, the content of SiO2 is 15 - 40 wt%, and the content of CaO is 10 - 30 wt%. A suitable material ratio is beneficial to the formation of a molten slag containing an olivine phase and promotes a further increase in the enrichment multiple of precious metals.

[0062] In the above embodiments, the weights of FeO, SiO2, and CaO are obtained by converting the contents of Fe, Si, and Ca elements in the mixture. The contents of Fe, Si, and Ca elements can be measured by instrument devices such as an inductively coupled plasma mass spectrometer. It should be noted that the FeO mentioned does not mean that the Fe element can only exist in the form of FeO in the mixture, and the Fe element can also exist in other forms in various materials. For example, it exists in the mixture in the form of Fe2O3. When calculating the weight of FeO, the weight of the Fe element in Fe2O3 and the molar ratio of the Fe element to FeO can be used to calculate the weight of FeO.

[0063] Furthermore, precious metal-containing materials, smelting aids and calcium-containing slag-forming agents are added so that when the Fe, Si and Ca elements in the mixture are smelted to form FeO, SiO2 and CaO, the proportions of FeO, SiO2 and CaO satisfy the following requirements: based on the total weight of FeO, SiO2 and CaO, the content of FeO is 30-60wt%, the content of SiO2 is 15-40wt% and the content of CaO is 10-30wt%.

[0064] In some embodiments, the olivine phase is a 2(Fe, Ca)O-SiO2 phase.

[0065] In some embodiments, the molten slag containing the olivine phase appears glassy.

[0066] In some embodiments, the precious metal-containing material is selected from at least one of hematite slag, anode mud, smelting slag and associated precious metal ores. In some embodiments, the precious metal-containing material is hematite slag produced by the iron removal process after nickel matte leaching.

[0067] In some specific examples of the present application, the composition of the precious metal-containing material includes: Fe 15-25wt%, Ni 1-2.5wt%, Si 10-20wt%, Cu 0.05-0.4wt%, and precious metal 500-2000g / t.

[0068] In some embodiments, the composition of the precious metal includes Pt 560-580g / t, Pd 420-430g / t, Ag 40-45g / t, Au 90-93g / t, Ir 71-73g / t, and Rh 84-86g / t. In some embodiments, the iron-containing material contains a fusion of multiple metal sulfides. In some specific examples, the fusion is an intermediate product matte produced in the smelting process (matte smelting or sulfide reduction smelting, etc.) of non-ferrous metals such as copper and nickel.

[0069] In some embodiments, the calcium-containing slag-forming agent is calcium oxide. Selecting this type of calcium-containing slag-forming agent not only increases the fluidity of the system and the capture amount of precious metals, but also reduces the melting point to achieve the purpose of saving energy.

[0070] In some embodiments, the silicon-containing material is silicon dioxide.

[0071] In some embodiments, the iron-containing material is selected from at least one of hematite, matte nickel, nickel matte, nickel iron, scrap iron and nickel slag. On the one hand, the above-mentioned iron-containing materials are widely sourced, low-cost and easy to obtain; at the same time, the method provided in this application enables further recycling of the iron-containing materials. On the other hand, the platinum group metals in the precious metal-containing materials have similar lattice structures and unit cell parameters to iron elements and the heavy non-ferrous metal nickel, and can form continuous solid solution alloys or intermetallic compounds within a wide composition range. Moreover, the matte in the smelting aids and the precious metal-containing materials have metalloid properties and also have a trapping effect on precious metals.

[0072] The selection of appropriate material types and ratios can further improve the trapping efficiency of precious metals, adjust the proportion and composition of the precious metal enrichment phase, which is beneficial to the subsequent leaching process, and a large amount of iron and nickel elements can be leached under normal pressure.

[0073] In some embodiments, the iron-containing material is hematite. By adding hematite to adjust the proportion of iron oxide in the mixture, it is easier to form a molten slag containing olivine phase.

[0074] In some embodiments, the composition of the hematite includes: Fe 60 - 65 wt%, Ni 1 - 3 wt%, Si 0.01 - 0.04 wt%, Cu 0.1 - 0.2 wt%.

[0075] In some embodiments, the composition of the matte nickel includes: Fe 52 - 56 wt%, Ni 17 - 20 wt%, Si 0.01 - 0.04 wt%, Cu 0.02 - 0.05 wt%.

[0076] In some embodiments, the composition of the nickel matte includes: Fe 3.5 - 3.9 wt%, Ni 68 - 72 wt%, Si 0.008 - 0.015 wt%, Cu 0.1 - 0.15 wt%.

[0077] In some embodiments, the reducing agent is selected from at least one of activated carbon, graphite, coke powder and coal powder.

[0078] The dosage of the reducing agent can be adjusted according to the amount of the precious metal-containing material to be treated. In some embodiments, based on the total weight of the precious metal-containing material, the dosage of the reducing agent is 1 - 10 wt%, for example, it can be any value among 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt%. In some embodiments, the dosage of the reducing agent is 2 - 5 wt%, for example, it can be any value among 2 wt%, 3 wt%, 4 wt% or 5 wt%.

[0079] In some embodiments, based on the total weight of the mixture, the dosage of the precious metal-containing material is 40-80 wt%, the dosage of the smelting aid is 15-50 wt%, and the dosage of the calcium-containing slag former is 5-10 wt%.

[0080] In some embodiments, the conditions for the smelting treatment include: the smelting temperature is 1100-1300 °C. If the smelting temperature is too high, it will cause incomplete phase separation between the molten slag and the enrichment phase, resulting in poor precious metal enrichment effect; while if the temperature is too low, it is difficult to form a molten slag containing olivine, and some capture components have not completely become liquid, so that the precious metals cannot be completely enriched into the assay button.

[0081] In some embodiments, the conditions for the smelting treatment include: the smelting time is 4-6 h. Controlling appropriate temperature and time is more likely to form a molten slag containing olivine phase and achieve a higher enrichment multiple.

[0082] In some embodiments, the method for enriching precious metals further includes contacting an acidic substance with the enrichment phase to carry out an acid leaching reaction to obtain an acid leaching product.

[0083] In some embodiments, the steps of the acid leaching reaction include: preparing the enrichment phase into a slurry, and contacting the slurry with an acidic substance to carry out an acid leaching reaction. Pulping can prevent agglomeration, and the reaction with acid is more sufficient after uniform dispersion. In addition, it can also reduce the leaching of precious metals and improve safety.

[0084] In some embodiments, the solid content in the slurry is 12.5-25 wt%.

[0085] In some embodiments, the acidic substance is selected from at least one of hydrochloric acid, nitric acid, and sulfuric acid with a concentration ≥ 98 wt%. In some embodiments, a sulfuric acid system is used for the acid leaching reaction, without introducing impurity anions such as chloride ions and nitrate ions, and the produced aqueous solution can be recycled to the system. The whole process has a short flow, low loss, low cost, and a high precious metal enrichment multiple.

[0086] In some embodiments, the addition amount of the acidic substance makes the initial pH value of the system 0-2.5, for example, it can be any value among 0, 0.5, 1, 1.5, 2, or 2.5.

[0087] In some embodiments, the conditions for the acid leaching reaction include: the temperature is 80-100 °C, and the time is 1-2 h.

[0088] In some embodiments, before preparing the enrichment phase into a slurry, the enrichment phase is first crushed. The present application has no special requirements for the crushing method. For example, a grinding device, a sample preparation pulverizer, or a water quenching and atomizing device can be used for crushing.

[0089] In some embodiments, the method for enriching noble metals further includes contacting the acid leaching product with an oxidant to carry out an oxidation reaction, obtaining a nickel-containing solution and a noble metal concentrate. Through oxygen leaching, the enrichment multiple of noble metals can be greatly increased. The noble metal content in the obtained noble metal concentrate can reach more than 100 kg / t, and the recovery rate of iron and nickel elements reaches more than 98 wt%. At the same time, in this reaction process, the uncompletely oxidized sulfide ions are oxidized into sulfate radicals. In some embodiments, the nickel-containing solution can be used to produce nickel ferrous sulfate.

[0090] In some embodiments, as Figure 1 shown, the method for enriching noble metals includes the following steps:

[0091] In the presence of a reducing agent, contacting and mixing a noble metal-containing material, a smelting assistant, and a calcium-containing slag-forming agent to obtain a mixture;

[0092] Subjecting the mixture to a smelting treatment to obtain a molten slag containing olivine phase and an enriched phase containing noble metals;

[0093] Contacting an acidic substance with the enriched phase to carry out an acid leaching reaction to obtain an acid leaching product;

[0094] Contacting the acid leaching product with an oxidant to carry out an oxidation reaction to obtain a nickel-containing solution and a noble metal concentrate.

[0095] In some embodiments, the oxidant is selected from at least one of ozone, sodium persulfate, and sodium peroxydisulfate.

[0096] In some embodiments, the conditions of the oxidation reaction include: the feeding flow rate of the ozone is 200 - 600 mL / min.

[0097] In some embodiments, the weight ratio of the acid leaching product to the sodium persulfate is 1:0.8 - 1.2.

[0098] In some embodiments, the weight ratio of the acid leaching product to the sodium peroxydisulfate is 1:0.8 - 1.2.

[0099] In some embodiments, the time of the oxidation reaction is 6 - 8 h.

[0100] In some embodiments, the method for enriching noble metals further includes: subjecting the nickel-containing solution obtained from the oxidation reaction to a purification treatment to obtain a nickel salt solution.

[0101] It can be understood that the purification treatment of the nickel-containing solution includes removing iron, aluminum, copper, etc.

[0102] In some embodiments, the noble metal content in the noble metal concentrate is ≥95 kg / t, preferably ≥100 kg / t, and more preferably 110 - 125 kg / t.

[0103] The present application will be described in detail below with reference to examples. In the following examples, unless otherwise specified, the raw materials, equipment, and instruments involved are all commercially available products.

[0104] In the following examples, the precious metal-containing material presents unevenly sized red lumps, with a moisture content of 52.18 wt%, and the rest are dry basis results except for moisture. The component contents are shown in Table 1.

[0105] Table 1

[0106]

[0107] In the following examples, the test methods involved are as follows:

[0108] Content of each element: Obtained by testing with an inductively coupled plasma mass spectrometer of model ICP7000;

[0109] Moisture content: Obtained by testing with an electrothermal constant temperature drying oven of model 202-2EBS;

[0110] XRD pattern: Obtained by detecting with a Bruker D8 X-ray powder diffractometer after crushing and grinding the molten slag.

[0111] The calculation formulas involved are as follows:

[0112] Enrichment multiple (times) of precious metals = Element content after enrichment / Element content before enrichment;

[0113] Leaching rate of element (wt%) = Element content in nickel-containing solution / Element content in assay button;

[0114] Total recovery rate of element (wt%) = Element content in nickel-containing solution / Element content in precious metal-containing material.

[0115] Example 1

[0116] Ferronickel and dried hematite are used as iron-containing materials, and their component contents are shown in Table 2.

[0117] Table 2

[0118] Composition Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) Moisture (wt%) Matte 54.20 18.84 0.02 0.04 0.00 Hematite 63.00 2.23 0.03 0.14 0.00

[0119] And the following method is used to enrich precious metals:

[0120] (1) Take 200 g of dried and ground precious metal-containing material, 35 g of hematite, 28.2 g of calcium oxide, and 6 g of activated carbon, mix them evenly in a square crucible, and then add 25 g of ferronickel powder and mix evenly to obtain a mixed material; the addition amounts of each material satisfy: convert the weights of Fe, Si, and Ca elements in the material into the weights of FeO, SiO2, and CaO, and based on the total weight of the three, the content of FeO is 50 wt%, the content of SiO2 is 35 wt%, and the content of CaO is 15 wt%.

[0121] (2) Place the crucible containing the mixed material obliquely in a muffle furnace for smelting treatment, set the temperature at 1300 °C and melt for 4 h. After taking out the crucible and cooling it to room temperature, take out the mixed material, separate the molten slag containing the olivine phase and the assay button (the molten slag and the assay button are as shown in Figure 2 , and the XRD pattern of the molten slag is shown in Figure 8 ), and weigh and take samples for inspection respectively. The analysis results of each component are shown in Table 3;

[0122] (3) Grind and crush the obtained assay button, take 50 g and put it into a 500 mL beaker, add 300 mL of pure water, then add sulfuric acid to control the pH of the solution to 1.0, and carry out acid leaching at 85 °C for 1.5 h until the pH of the solution tends to be stable to obtain an acid leaching product;

[0123] (4) Insert an aeration tube into the beaker and introduce ozone at a flow rate of 500 mL / min for oxygen leaching, react for 7 h, and filter to obtain a nickel-containing solution and a precious metal concentrate. The analysis results of each component are shown in Table 4.

[0124] Table 3

[0125] Composition Mass (g) Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) Ca (wt%) S (wt%) Gold assay button 83.79 55.47 10.62 0.05 0.28 0.36 0.82 Molten slag 159.24 1.28 0.12 9.24 0.04 5.84 9.04

[0126] Table 4

[0127]

[0128] From Figure 8 it can be seen that after the raw materials are melted, an olivine slag is formed, and the CaFeSiO4 phase, Ca2SiO4 phase, and CaO phase appear, indicating that the olivine slag may be mainly based on the CaO-FeO-SiO2 ternary system, and the mineral phase is centered around calcium iron olivine and calcium silicate.

[0129] As can be seen from Table 3 and Table 4, after the noble metal-containing materials are proportioned and smelted, silicon and calcium elements enter the slag phase (molten slag), and the noble metals are captured and enter the assay button. The noble metals are enriched by about 2.39 times during the whole process. The 50g assay button is then subjected to acid leaching and oxygen leaching respectively, and the noble metals are further enriched. Most of the nickel and iron elements in the assay button are leached out. Finally, a 465 mL nickel-containing solution and 1.2 g of noble metal concentrate are obtained. The noble metals are enriched by 41.67 times during the whole acid leaching and oxygen leaching process. The leaching rates of nickel and iron elements in the assay button reach 98.89 wt% and 99.80 wt% respectively. The whole process of this method successfully enriches the noble metals by 99.45 times, and the total recovery rates of iron and nickel elements reach 63.35 wt% and 96.81 wt% respectively.

[0130] To verify the experimental results, the noble metal concentrate was sent for inspection, and the analysis results are shown in Table 5. The actual noble metals are enriched by 94.67 times. The possible reason is that the noble metals are unevenly distributed in the noble metal-containing materials and cannot be completely captured during the melting process and enter the slag phase.

[0131] Table 5

[0132] Composition Pt (g / t) Pd (g / t) Ag (g / t) Au (g / t) Ir (g / t) Rh (g / t) Precious metal concentrate 57318 38196 3907 8685 6432 7321

[0133] Example 2

[0134] Take nickel matte and dried hematite (the same as in Example 1) as iron-containing materials, and the component content of nickel matte is shown in Table 6.

[0135] Table 6

[0136] Composition Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) Moisture (wt%) High-grade matte 3.76 70.04 0.01 0.12 0.00

[0137] And the following method is used to enrich noble metals:

[0138] (1) Take 150 g of dried and ground noble metal-containing materials, 75 g of hematite, 16.5 g of calcium oxide, and 5 g of activated carbon and mix them evenly in a square crucible. Then add 25 g of nickel matte powder and mix evenly to obtain a mixed material. The addition amounts of each material satisfy that the Fe, Si, and Ca elements in the materials are converted into the weights of FeO, SiO2, and CaO. Based on the total weight of the three, the content of FeO is 60 wt%, the content of SiO2 is 30 wt%, and the content of CaO is 10 wt%.

[0139] (2) Place the crucible containing the mixed material obliquely in a muffle furnace for smelting treatment. Set the temperature at 1200 °C and melt for 4 h. After taking out the crucible and cooling it to room temperature, take out the mixed material, separate the molten slag containing olivine phase and the assay button (as Figure 3 shown), and weigh and take samples for inspection respectively. The analysis results of each component are shown in Table 7;

[0140] (3) Grind and crush the obtained assay button, take 50 g and put it into a 500 mL beaker, add 300 mL of pure water, then add sulfuric acid to control the pH of the solution to 1.0, and carry out acid leaching at 85 °C for 1.5 h until the pH of the solution tends to be stable to obtain the acid leaching product;

[0141] (4) Insert an aeration pipe into the beaker, and introduce ozone at a flow rate of 500 mL / min for oxygen leaching, react for 7 h, filter to obtain a nickel-containing solution and precious metal concentrate, and the analysis results of each component are shown in Table 8.

[0142] Table 7

[0143] Composition Mass (g) Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) Ca (wt%) S (wt%) Gold assay button 97.56 50.12 21.84 0.16 0.26 0.22 2.95 Molten slag 139.64 19.64 0.32 16.42 0.04 8.24 8.73

[0144] Table 8

[0145]

[0146] As can be seen from Table 7 and Table 8, the precious metals are enriched by about 1.53 times during the entire smelting process; after the 50 g assay button undergoes acid leaching and oxygen leaching, the precious metals are further enriched to obtain 480 mL of nickel-containing solution and 0.85 g of precious metal concentrate. The precious metals are enriched by 58.82 times during the entire acid leaching and oxygen leaching process, and the leaching rates of nickel and iron elements in the assay button reach 98.57 wt% and 99.87 wt% respectively; the entire process of this method successfully enriches the precious metals by 90.44 times, and the total recovery rates of iron and nickel elements reach 64.00 wt% and 96.56 wt% respectively.

[0147] To verify the experimental results, the precious metal concentrate was sent for inspection, and the results are shown in Table 9. The actual precious metals are enriched by 91.68 times.

[0148] Table 9

[0149] Composition Pt (g / t) Pd (g / t) Ag (g / t) Au (g / t) Ir (g / t) Rh (g / t) Precious metal concentrate 52787 39341 3857 8048 6325 7656

[0150] Example 3

[0151] According to a method similar to that of Example 1, the difference is that waste nickel slag is used to replace the matte in Example 1, and the materials used are: 200 g of precious metal-containing material, 55 g of hematite, 28.4 g of calcium oxide, 6 g of activated carbon, and 25 g of waste nickel slag; among them, the component content of the waste nickel slag is shown in Table 10;

[0152] The rest are the same, and a molten slag containing olivine phase and an assay button (as Figure 4 shown) are obtained, and the analysis results of the components are shown in Table 11; the analysis results of the components in the nickel-containing solution and precious metal concentrate are shown in Table 12.

[0153] Table 10

[0154] Composition Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) Moisture (wt%) Waste nickel slag 3.78 49.56 0.03 5.4 13.08

[0155] Table 11

[0156]

[0157]

[0158] Table 12

[0159]

[0160] As can be seen from Table 11 and Table 12, the noble metals are enriched by about 2.02 times during the entire smelting process; the 50 g assay button is further enriched with noble metals through acid leaching and oxygen leaching, obtaining 480 mL of nickel-containing solution and 1.08 g of noble metal concentrate. The noble metals are enriched by 46.3 times during the entire acid leaching and oxygen leaching process, and the leaching rates of nickel and iron elements in the assay button reach 98.94 wt% and 99.43 wt% respectively; the entire process of this method successfully enriches the noble metals by 93.56 times, and the total recovery rates of iron and nickel elements reach 58.41 wt% and 95.15 wt% respectively.

[0161] To verify the experimental results, the noble metal concentrate was sent for inspection, and the analysis results are shown in Table 13. The actual noble metals are enriched by 92.79 times.

[0162] Table 13

[0163] Composition Pt (g / t) Pd (g / t) Ag (g / t) Au (g / t) Ir (g / t) Rh (g / t) Precious metal concentrate 54361 38964 3651 8248 6468 7746

[0164] Example 4

[0165] According to a method similar to that of Example 1, the difference is that the materials used are: 100 g of noble metal-containing material, 178 g of waste iron powder, 49 g of calcium oxide, and 3 g of activated carbon; the addition amounts of each material satisfy: converting the weights of Fe, Si, and Ca elements in the materials into the weights of FeO, SiO2, and CaO, and based on the total weight of the three, the content of FeO is 75 wt%, the content of SiO2 is 10 wt%, and the content of CaO is about 15 wt%; among them, the component content of the waste nickel powder is shown in Table 14;

[0166] The rest are the same, obtaining a molten slag containing olivine phase and an assay button, and the component analysis results are shown in Table 15; the component analysis results in the nickel-containing solution and the noble metal concentrate are shown in Table 16.

[0167] Table 14

[0168] Composition Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) S (wt%) Waste iron powder 96.84 0 0 0.52 0.61

[0169] Table 15

[0170] Composition Mass (g) Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) Ca (wt%) S (wt%) Gold assay button 172.43 78.47 0.96 0.01 0.56 0.12 0.82 Molten slag 128.54 43.42 0.12 11.94 0.04 26.84 4.76

[0171] Table 16

[0172]

[0173] As can be seen from Table 15 and Table 16, the noble metals are enriched by about 0.58 times during the entire smelting process; the 50 g assay button is further enriched with noble metals through acid leaching and oxygen leaching, obtaining 530 mL of nickel-containing solution and 0.38 g of noble metal concentrate. The noble metals are enriched by 131.58 times during the entire acid leaching and oxygen leaching process, and the leaching rates of nickel and iron elements in the assay button reach 99.7 wt% and 98.42 wt% respectively; the entire process of this method successfully enriches the noble metals by 76.31 times, and the total recovery rates of iron and nickel elements reach 70.59 wt% and 89.99 wt% respectively.

[0174] To verify the experimental results, the noble metal concentrate was sent for inspection, and the results are shown in Table 17. The actual enrichment of noble metals is 74.5 times.

[0175] Table 17

[0176] Composition Pt (g / t) Pd (g / t) Ag (g / t) Au (g / t) Ir (g / t) Rh (g / t) Precious metal concentrate 42670 30648 2864 6751 5648 7321

[0177] Comparative Example 1

[0178] According to a method similar to that of Example 1, the difference is that the smelting temperature in this comparative example is 1000 °C;

[0179] The rest are the same, obtaining a molten slag containing wollastonite phase and an assay button (as Figure 5 shown), and the component analysis results are shown in Table 18; the component analysis results in the nickel-containing solution and the noble metal concentrate are shown in Table 19.

[0180] Table 18

[0181] Mass (g) Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) Ca (wt%) Gold assay button 37.91 51.37 15.48 0.02 0.29 0.73 Molten slag 211.4 32.39 1.96 18.52 0.11 11.98

[0182] Table 19

[0183]

[0184] From Figure 5 it can be seen that after melting the noble metal-containing material, a fluffy and porous rectangular slag is obtained, and multiple small metal particles are embedded in the molten slag containing wollastonite phase.

[0185] As can be seen from Table 18 and Table 19, part of the nickel and iron elements remain in the molten slag. After separation, only 37.91 g of the assay button is obtained. The precious metals are enriched about 5.28 times during the entire smelting process. The 30 g assay button is further leached with acid and oxygen, and the precious metals are further enriched, obtaining 485 mL of nickel-containing solution and 3.44 g of precious metal concentrate. The precious metals are enriched 8.72 times during the entire acid leaching and oxygen leaching process, and the leaching rates of nickel and iron elements are 98.75 wt% and 99.51 wt% respectively. The entire process of this method successfully enriches the precious metals 46.0 times, and the total recovery rates of iron and nickel elements are 26.45 wt% and 63.45 wt% respectively.

[0186] To verify the experimental results, the precious metal concentrate was sent for inspection. The analysis results are shown in Table 20. The actual enrichment of precious metals is 41.51 times. The reason may be that the temperature fails to reach the melting point of the slag type, and nickel and iron are not completely melted, only capturing a small amount of precious metals, resulting in the loss of precious metals and a small enrichment multiple.

[0187] Table 20

[0188] Composition Pt (g / t) Pd (g / t) Ag (g / t) Au (g / t) Ir (g / t) Rh (g / t) Precious metal concentrate 23361 16964 1951 4248 3068 3846

[0189] Comparative Example 2

[0190] According to a method similar to that of Example 1, except that calcium oxide is not added during the smelting process in this comparative example;

[0191] The rest are the same, obtaining a molten slag containing wollastonite phase (as Figure 6 shown) and the assay button. The component analysis results are shown in Table 21; the component analysis results in the nickel-containing solution and the precious metal concentrate are shown in Table 22.

[0192] Table 21

[0193] Mass (g) Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) Ca (wt%) Gold assay button 72.82 31.34 9.24 0.02 0.21 0.02 Molten slag 160.68 31.31 1.45 19.04 0.07 0.05

[0194] Table 22

[0195]

[0196]

[0197] Compared with Examples 1 to 3, after melting the precious metal-containing material, irregular lumps are obtained. The upper layer of the molten slag is porous and fluffy, and there are small metal lumps remaining in some areas of the crucible (as Figure 6 shown).

[0198] From Figure 6As can be seen from Table 21 and Table 22, part of the nickel and iron elements remain in the molten slag. After separation, 72.82 g of assay buttons are obtained. During the entire smelting process, the precious metals are enriched by about 2.75 times. The 50 g assay buttons are further leached with acid and oxygen, and the precious metals are further enriched, obtaining 480 mL of nickel-containing solution and 2.62 g of precious metal concentrate. During the entire acid leaching and oxygen leaching process, the precious metals are enriched by 19.08 times. The leaching rates of nickel and iron elements in the assay buttons are 99.17 wt% and 99.58 wt% respectively. The entire process of this method successfully enriches the precious metals by 52.41 times, and the total recovery rates of iron and nickel elements are 31.10 wt% and 73.75 wt% respectively.

[0199] To verify the experimental results, the precious metal concentrate was sent for inspection. The analysis results are shown in Table 23. The actual enrichment factor of the precious metals is 61.17 times. The reason is that calcium oxide was not added during the melting process, resulting in a high melting point during melting and poor fluidity of the molten metal, failing to completely capture all the precious metals, leading to the loss of precious metals and a small enrichment factor.

[0200] Table 23

[0201] Composition Pt (g / t) Pd (g / t) Ag (g / t) Au (g / t) Ir (g / t) Rh (g / t) Precious metal concentrate 33361 26964 2951 6248 4068 5846

[0202] Comparative Example 3

[0203] According to a method similar to that of Example 1, the difference is that an equal amount of borax was added during the smelting process of this comparative example to replace calcium oxide in Example 1;

[0204] The rest are the same, obtaining a molten slag and assay buttons composed of wollastonite and olivine mixture (as Figure 7 shown), and the component analysis results are shown in Table 24; the component analysis results in the nickel-containing solution and precious metal concentrate are shown in Table 25.

[0205] Table 24

[0206] Composition Mass (g) Fe (wt%) Ni (wt%) Si (wt%) Cu (wt%) Ca (wt%) Gold assay button 109.67 52.36 9.14 1.15 0.27 0.01 Molten slag 161.86 18.78 0.91 18.64 0.04 0.02

[0207] Table 25

[0208]

[0209] As can be seen from Table 24 and Table 25, during the entire smelting process, the precious metals are enriched by 1.82 times. The 50 g assay buttons are further leached with acid and oxygen, and the precious metals are further enriched, obtaining 485 mL of nickel-containing solution and 1.28 g of precious metal concentrate. The leaching rates of nickel and iron elements in the assay buttons are 99.14 wt% and 98.85 wt% respectively. During the entire acid leaching and oxygen leaching process, the precious metals are enriched by 39.06 times. The entire process of this method successfully enriches the precious metals by 71.23 times, and the total recovery rates of nickel and iron elements are 83.33 wt% and 58.44 wt% respectively.

[0210] In order to verify the experimental results, the precious metal concentrate was sent for inspection, and the analysis results are shown in Table 26. The actual precious metal enrichment was 72.47 times. Compared with the embodiment, it can be seen that using borax instead of calcium oxide for melting slag will form unstable olivine phase molten slag, and there will be multiple scattered metal buckles mixed with slag phase on the surface of the test buckle, resulting in precious metal loss.

[0211] Table 26

[0212] Composition Pt (g / t) Pd (g / t) Ag (g / t) Au (g / t) Ir (g / t) Rh (g / t) Precious metal concentrate 44768 28867 3017 5946 4861 5834

[0213] Comparative Example 4

[0214] This comparative example is described by citing Example 1 of the specification disclosed in CN107604170A. A method for separating and enriching precious metals from low-grade nickel matte chloride leaching residue in this scheme is as follows:

[0215] The composition of low nickel matte chloride leaching slag is shown in Table 27.

[0216] Table 27

[0217] Ni (wt%) Cu (wt%) Fe (wt%) Au (g / t) Pd (g / t) Pt (g / t) S (wt%) 0.76 0.95 0.91 19 21 52.3 87.62

[0218] The specific experimental steps are:

[0219] (1) Fire method for removing elemental sulfur: The low-grade nickel matte chloride leaching residue is roasted in a rotary kiln to obtain desulfurized slag at a temperature of 1000°C for 1 h. The composition analysis of the desulfurized slag is shown in Table 28.

[0220] Table 28

[0221] Ni (wt%) Cu (wt%) Fe (wt%) Au (g / t) Pd (g / t) Pt (g / t) S (wt%) 4.39 7.02 15.35 182.3 708.5 2770 10.33

[0222] (2) Fire method for desiliconization, impurity removal and precious metal capture: desulfurization slag, precious metal capture agent, solvent and reducing agent are mixed evenly in the following weight ratio: desulfurization slag: precious metal capture agent: solvent: reducing agent is equal to 100:50:15:8, wherein the precious metal capture agent is a mixture of converter slag and secondary nickel concentrate, the solvent is lime powder, and the reducing agent is pulverized coal. After the desulfurization slag is mixed evenly with the precious metal capture agent, solvent and reducing agent, an electric arc furnace is used to smelt at a temperature of 1200°C for 3 hours. After the smelting is completed, molten slag and precious metal matte are obtained, and the molten slag and precious metal matte are discharged from different discharge ports of the electric arc furnace respectively. The composition analysis of the precious metal matte is shown in Table 29, and the composition analysis of the molten slag is shown in Table 30.

[0223] Table 29

[0224] Ni (wt%) Cu (wt%) Fe (wt%) Au (g / t) Pd (g / t) Pt (g / t) S (wt%) 52.1 20.8 12.9 584 2230 7831 8.92

[0225] Table 30

[0226] Ni (wt%) Cu (wt%) Fe (wt%) Au (g / t) Pd (g / t) Pt (g / t) 10.38 2.31 15.3 6.81 6.12 7.83

[0227] (3) Water quenching and atomization: Put the precious metal matte into a 200kw water quenching metal powder making equipment. After remelting the precious metal matte at 1350 °C, obtain precious metal matte powder with a particle size of -150 mesh through water quenching and atomization, so as to improve the leaching efficiency in the subsequent process.

[0228] (4) Oxygen pressure acid leaching to remove copper and nickel: Put the precious metal matte powder into a pressurized reaction kettle filled with dilute sulfuric acid solution for oxygen pressure acid leaching to selectively leach and separate base metals. The solid-liquid ratio is 1:5, the working pressure is 1.2 MPa, the concentration of dilute sulfuric acid is 150 g, the temperature is 150 °C, and the oxygen flow rate is 20 Nm 3 , the oxygen passing time is 5 h. After the reaction, filter to obtain oxygen pressure acid leaching residue and leaching solution mainly containing nickel sulfate and copper sulfate components. The component analysis of the oxygen pressure acid leaching residue is shown in Table 31, and the component analysis of the leaching solution is shown in Table 32.

[0229] Table 31

[0230] Ni (wt%) Cu (wt%) Fe (wt%) Au (g / t) Pd (g / t) Pt (g / t) 0.97 0.56 0.27 1380 6000 18200

[0231] Table 32

[0232] Ni (g / L) Cu (g / L) Fe (g / L) Au (g / L) Pd (g / L) Pt (g / L) 78 43 22 0.0008 0.0005 0.0005

[0233] (5) Washing: Wash the oxygen pressure acid leaching residue to neutral to obtain precious metal concentrate, which can be used as raw material for purifying precious metal products.

[0234] In this scheme, the S content in the raw material is 87.62 wt%, and the precious metal matte still contains 8.92 wt% of S after desulfurization. Therefore, high-pressure oxygen leaching is adopted subsequently to leach nickel, copper, and iron elements. Its process flow is long, the operation is complex, and the enrichment multiple of precious metals is low.

[0235] From the data of the foregoing Examples 1 to 4, it can be seen that the precious metal content in the raw material of the present application is relatively high, the S content is 7.54 wt%, and the Si content is 15.38%. After the mixture is subjected to smelting treatment by the method provided by the present application, the S content is only 0.8 - 3 wt%, and the Si content is only 0.01 - 0.16 wt%. The sulfur removal rate and silicon removal rate are significantly improved, making the proportion of sulfides in the obtained precious metal-rich phase very small and the alloy phase relatively large; further adopting acid leaching reaction and oxidation reaction, the leaching rates of nickel and iron elements both reach more than 98 wt%. The total enrichment multiple of precious metals in the entire process of this method reaches up to more than 90 times, the total recovery rates of iron and nickel elements reach 58 wt% or more and 89 wt% or more respectively, and the content of precious metals in the precious metal concentrate reaches 95 kg / t or more, and the highest reaches 100 kg / t or more.

[0236] The preferred embodiments of the present application are described in detail above. However, the present application is not limited thereto. Within the technical concept scope of the present application, various simple modifications can be made to the technical solutions of the present application, including combinations of each technical feature in any other suitable manner. These simple modifications and combinations should also be regarded as the content disclosed by the present application and fall within the protection scope of the present application.

Claims

1. A method for enriching precious metals, characterized in that, The method includes: In the presence of a reducing agent, bringing a noble metal-containing material, a smelting aid, and a calcium-containing slag-forming agent into contact and mixing them to obtain a mixed material; Subjecting the mixed material to a smelting treatment to obtain a molten slag containing an olivine phase and an enriched phase containing noble metals.

2. The method according to claim 1, wherein The smelting aid includes at least one of an iron-containing material and a silicon-containing material.

3. The method according to claim 1, characterized in that, The addition amounts of the noble metal-containing material, the smelting aid, and the calcium-containing slag-forming agent satisfy: based on the total weight of FeO, SiO2, and CaO, the content of FeO is 30 - 60 wt%, the content of SiO2 is 15 - 40 wt%, and the content of CaO is 10 - 30 wt%.

4. The method according to claim 1, wherein The method satisfies at least one of the following conditions: A. The olivine phase is a 2(Fe, Ca)O - SiO2 phase; B. The noble metal-containing material is selected from at least one of hematite slag, anode mud, smelting slag, and associated noble metal ore; C. The composition of the noble metal-containing material includes: Fe 15 - 25 wt%, Ni 1 - 2.5 wt%, Si 10 - 20 wt%, Cu 0.05 - 0.4 wt%, noble metals 500 - 2000 g / t; D. The composition of the noble metals includes: Pt 560 - 580 g / t, Pd 420 - 430 g / t, Ag 40 - 45 g / t, Au 90 - 93 g / t, Ir 71 - 73 g / t, Rh 84 - 86 g / t.

5. The method according to any one of claims 1-4, characterized in that, The method satisfies at least one of the following conditions: A. The calcium-containing slag-forming agent is calcium oxide; B. The silicon-containing material is silicon dioxide; C. The iron-containing material is selected from at least one of hematite, matte nickel, nickel matte, nickel iron, scrap iron, and nickel slag; D. The composition of the hematite includes: Fe 60 - 65 wt%, Ni 1 - 3 wt%, Si 0.01 - 0.04 wt%, Cu 0.1 - 0.2 wt%; E. The composition of the matte nickel includes: Fe 52 - 56 wt%, Ni 17 - 20 wt%, Si 0.01 - 0.04 wt%, Cu 0.02 - 0.05 wt%; F. The composition of the nickel matte includes: Fe 3.5 - 3.9 wt%, Ni 68 - 72 wt%, Si 0.008 - 0.015 wt%, Cu 0.1 - 0.15 wt%.

6. The method according to any one of claims 1-4, characterized in that, The method satisfies at least one of the following conditions: A. The reducing agent is selected from at least one of activated carbon, graphite, coke powder, and pulverized coal; B. Based on the total weight of the noble metal-containing material, the dosage of the reducing agent is 1 - 10 wt%; C. Based on the total weight of the mixed material, the dosage of the noble metal-containing material is 40 - 80 wt%, the dosage of the smelting aid is 15 - 50 wt%, and the dosage of the calcium-containing slag-forming agent is 5 - 10 wt%; D. The conditions for the smelting treatment include: the smelting temperature is 1100 - 1300 °C; E. The conditions for the smelting treatment include: the smelting time is 4 - 6 h.

7. The method according to any one of claims 1 to 4, characterized in that, The method satisfies at least one of the following conditions: A. It further includes bringing an acidic substance into contact with the enriched phase to carry out an acid leaching reaction to obtain an acid leaching product; B. The steps of the acid leaching reaction include: preparing the enriched phase into a slurry, and contacting the slurry with an acidic substance for the acid leaching reaction; C. The acidic substance is selected from at least one of hydrochloric acid, nitric acid, and sulfuric acid with a concentration ≥ 98 wt%; D. The addition amount of the acidic substance is such that the initial pH value of the system is 0 - 2.5; E. The conditions of the acid leaching reaction include: the temperature is 80 - 100 °C, and the time is 1 - 2 h.

8. The method according to claim 7, wherein The method satisfies at least one of the following conditions: A. It further includes contacting the acid leaching product with an oxidant to carry out an oxidation reaction to obtain a nickel-containing solution and a precious metal concentrate; B. The oxidant is selected from at least one of ozone, sodium persulfate, and sodium peroxydisulfate; C. The feeding flow rate of the ozone is 200 - 600 mL / min; D. The weight ratio of the acid leaching product to sodium persulfate is 1:0.8 - 1.2; E. The weight ratio of the acid leaching product to sodium peroxydisulfate is 1:0.8 - 1.2; F. The time of the oxidation reaction is 6 - 8 h.

9. The method according to claim 8, wherein The method further includes: performing impurity removal treatment on the nickel-containing solution to obtain a nickel salt solution.

10. The method according to claim 8 or 9, characterized in that The precious metal content in the precious metal concentrate ≥ 95 kg / t.

Citation Information

Patent Citations

  • Method for separating enriched precious metals from low ice nickel chloridized leaehing residue

    CN107604170A